Water Security Across the Gender Divide (Water Security in a New World,, 2018)
This book examines water security as a prime example of how the economic, socio-cultural and political-normative systems that regulate access to water reflect the evolving and gendered power relations between different societal groups. Access to water is characterized by inequalities: it depends not only on natural water availability, but also on the respective socio-political context. It is regulated by gender-differentiated roles and responsibilities towards the resource, which are strongly influenced by, among others, tradition, religion, customary law, geographical availability, as well as the historical and socio-political context. While gender has been recognized as a key intervening variable in achieving equitable water access, most studies fail to acknowledge the deep interrelations between social structures and patterns of water use. Proof of these shortcomings is the enduring lack of data on water accessibility, availability and utilization that sufficiently acknowledges the relational nature of gender and other categories of power and difference, like class and socioeconomic status, as well as their comprehensive analysis. This book addresses this major research gap.